Effect of knowledge management on organizational performance: A systematic literature review - Payal, R.; M. Roma, Debnath (Journal of General Management Research, 2015)
This paper aims to identify the state of the art related to the research problem 'The effect of Knowledge Management on Organizational Performance'. The systematic literature review includes 42 papers published between 2010 and 2012. The selected papers were classified according to research approach used, the country and industry of the sample population, research parameters/constructs studied, Data Analysis and software tools used and the research gaps in the inspected studies. The paper is the first effort towards a systematic literature review of the research problem. The paper can act as a starting point for future researches on the research problem.